Lexical vs. Structural Presuppositions in the Struggle between Virtue and Vice in Selected Dramatic Passages from Nathaniel Hawthorne’s The Scarlet Letter: Syntactico-Pragmatic Approach - Salahuddin, Usama (Jordan Journal of Modern Languages & Literatures, 2025)
This analytical-descriptive research attempts to investigate the relationship between the six types of presuppositions classified by George Yule (1996), the syntactic structure through which they are triggered, and the speaker’s intention behind triggering them in Nathaniel Hawthorne’s The Scarlet Letter. The paper discovers which types of presuppositions are more appropriate to be conveyed by specific syntactic structures and parts of speech to fulfill some specific intentions more successfully. It also investigates how the different motives of the main characters of the novel, Dimmesdale, Hester, and Chillingworth, result in different types of presuppositions and syntactic structures to fulfill the pragmatic purposes needed. The research is applied to 216 presuppositions detected in 50 dramatic passages selected from the most controversial situations that brought the three main characters together, the wife, the paramour and the husband; such situations are required to be interweaved very carefully and to present the characters as being very cautious about the presuppositions triggered by their utterances not to reveal the secrets they hide. Keywords: presupposition, trigger, syntactic structure, lexical level, structural level, speaker’s intention Hightlights: The research attempts to investigate the connection among the presuppositions triggered in Nathaniel Hawthorne’s The Scarlet Letter, their syntactic structure, and the speaker’s intention behind triggering them. The research proves that factive presuppositions tend to be largely triggered to state something through declarative sentences, structural presuppositions to imply something cleverly through AvCls. The research also proves that non-factive and counter-factual presuppositions tend to be largely triggered to trick or distract the addressee through interrogative sentences, and lexical and existential presuppositions to pitch an idea through NPs. The research proves established some connection between the presuppositions triggered by the three characters via certain syntactic structures go in line with their perspectives of life and their purposes. The research proves that presuppositions that serve purposes fulfilled because of human nature are proven to be employed through long structures, while those pre-planned out of a real need are done with careful selections of lexemes.